Genotypic analysis of drug-resistant tuberculosis in Ghana: Insights into pre-XDR and XDR-TB - Stephen Ofori Yirenkyi; Osmanu Taufik; Roger Laryea; Amanquador Acquah-Keelson; Japheth Awuletey Opintan; Gloria Ivy Mensah (PLoS ONE, 2025)
Background The emergence of Extensively Drug Resistant (XDR) and Pre-extensively drug resistant (Pre-XDR) tuberculosis (TB) threatens the management of multidrug-resistant tuberculosis (MDR) patients and impacts negatively on TB control programs, especially in developing countries like Ghana. The first case of XDR-TB in Ghana was reported in 2018. There is however inadequate data on the burden of XDR-TB and pre-XDR-TB and their associated resistant mutations in Ghana. The study sought to provide baseline data on the burden of pre-XDR-TB and XDR-TB among MDR TB cases in Ghana. It also determined the mutations responsible for pre-XDR/ XDR-TB, for clinical and programmatic management of pre-XDR/ XDR-TB in Ghana. Methods One hundred and seventy-one (171) archived clinical MDR isolates obtained from TB patients across Ghana between January 2016 and December 2020 were retrieved. The isolates were retested to confirm their phenotypic and genotypic susceptibility to the first and second-line anti-TB drugs using the BACTEC MGIT system and Genotype MTBDRplus, MTBDRsl, line probe assays respectively. Results Most of the 171 isolates came from 7 regions; the highest (39.5%) from Eastern, followed by Greater Accra region (19.8%). Most of the isolates were from male TB patients (78.9%). Of the 171 archived isolates, 81 (47.4%) were confirmed to be MDR, 6 (7.4%) were Pre-XDR-TB but no XDR-TB was detected. The katG S315T1 (33, 73.3%) and rpoB S531L (31, 42.5%) were the predominant mutations observed among isoniazid and rifampicin resistant isolates respectively. Many of the mutations and amino acid changes that caused pre-XDR-TB were gyrAWT3 + gyrAMUT3A and gyrAMUT3A (D94A) (50%) for fluoroquinolone. The other detected mutations with their amino acid changes were gyrA MUT1 (A90V), gyrAWT3 + gyrA MUT3C (D94G) and gyrA MUT2 (S91P) (16.7%) for fluoroquinolones and rrWT2 (position 1484) (33.3%) and rrs MUT2 (G1484T) (16.7%) for aminoglycosides. Conclusion The predominant mutations associated with pre-XDR-TB were D94A and C1402T for fluoroquinolone and aminoglycosides resistance respectively. The proportion of pre-XDR-TB among MDR-TB patients in Ghana was 7.4%; however, no XDR-TB was detected. A sustained surveillance of pre-XDR-TB and XDR-TB is recommended.